Los Incentivos Tributarios en el sector turístico y su efecto en la planificación financiera de la provincia de Chimborazo en el periodo 2015-2020. - Campaña Castellano, Wendy Thalía (2023)
The main objective of this research is to carry out an analysis of the influence of tax incentives on the financial planning of taxpayers who are part of the tourism sector in the province of Chimborazo during the period 2015-2020, it is important to state that the development of the The work was in several stages, the first stage of the project includes the context of the variables under study, where the reader will know the subject in depth and will establish a qualitative analysis of the information, as well as the base author of this investigative work, a second stage was the methodology for collecting field information and quantitative research.